Pelatihan Bahasa Inggris Pariwisata Komunikatif bagi Anggota Karang Taruna Tunas Muda Pekon Kiluan Negeri Kabupaten Tanggamus - Sinaga, Tuntun; Sutarsyah, Cucu; Suparman, Ujang; Putrawan, Gede Eka (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Teluk Kiluan located in Pekon (Village) Kiluan Negeri, Kelumbayan District, Tanggamus Regency, Lampung Province, has the potential to become an international class tourist destination since foreign tourists have started visiting this area. To make the interaction between foreign tourists with the local people and tourism practitioners run well, the local human resources (local people and tourism practitioners) are required to inevitably communicate in English. Therefore, the purpose of the community service was to help the local government, local people and tourism practitioners to communicate and convey information correctly to foreign tourists visiting Teluk Kiluan through a program called communicative English for tourism training. The participants of this event were the local people and tourism practitioners in Teluk Kiluan. To solve the problem faced by the local people and tourism practitioners due to lack of English for tourism mastery, some training methods were used including: (1) presentations on the importance of English as a lingua franca in the field of tourism, and (2) a workshop on communicative English for tourism through simulations, dialogues, and role playing, as well as discussions. Based on the score of each participant in the pre-test and post-test, there was an increase in the results before and after the training was carried out. They had the confidence to properly communicate and interact with foreign tourists. Besides, according to semi-structured interviews, the participants were satisfied with the event. Thus, it can be said that they derive much benefit from their participation in the training.